Variation in cardiovascular magnetic resonance myocardial contouring: Insights from an international survey - Moody, William E. (J Magn Reson Imaging, 2019)
Level of Evidence: 5 Technical Efficacy Stage: 2 J. Magn. Reson. Imaging 2019;50:1336–1338.